Angiotensin-Converting Enzyme Inhibitors/Angiotensin Receptor Blockers: Anti-arrhythmic Drug for Arrhythmogenic Right Ventricular Cardiomyopathy - Tu, Bin; Wu, Lingmin; Zheng, Lihui; Liu, Shangyu; Sheng, Lishui; Liu, Limin; Zhu, Zhenghui; Yao, Yan (Frontiers in Cardiovascular Medicine, 2021)
Background: Current treatment guidelines for arrhythmogenic right ventricular cardiomyopathy (ARVC) mainly emphasize on prevention of ventricular arrhythmic events. Despite the progressive nature of ARVC, therapeutic options focusing on decelerating disease progression are scarce. Methods and results: This retrospective observational cohort study included 311 patients [age, 39.1±14.4 years; male, 233 (74.9%)] with a definite diagnosis of ARVC as determined by the 2010 Task Force Diagnostic Criteria. Among them, 113 patients (36.3%) received ACEI/ARB treatment. Disease progression was evaluated according to repeat transthoracic echocardiograms with a linear mixed model. Patients receiving ACEI/ARB treatment were associated with slower disease progression reflected by a gradual decrease in tricuspid annular plane systolic excursion than those not receiving ACEI/ARB treatment (0.37 vs. 0.61 mm per year decrease, P < 0.001) and slower dilation of the right ventricular outflow tract (0.57 vs. 1.06 mm per year increased, P = 0.003). Cox proportional hazard regression models were used to evaluate the association between life-threatening ventricular tachycardia events and ACEI/ARB treatment. A reduced risk of life-threatening ventricular arrhythmia was associated with ACEI/ARB treatment compared to that without ACEI/ARB treatment (adjusted HR: 0.71, 95% CI: 0.52–0.96, P = 0.031). Conclusions: ACEI/ARB treatment is associated with slower disease progression and a lower risk of life-threatening ventricular arrhythmia in patients with ARVC. Delaying disease progression may pave way for reducing life-threatening ventricular arrhythmia risk.